Prevalence and projections of diabetes and pre-diabetes in adults in Sri Lanka--Sri Lanka Diabetes, Cardiovascular Study (SLDCS). - Katulanda, P; Constantine, G; Mahesh, J; Sheriff, R; Seneviratne, R; Wijeratne, S; Wijesuriya, M; McCarthy, M; Adler, A; Matthews, DR (2008)
AIMS: To determine the prevalence of diabetes mellitus and pre-diabetes (impaired fasting glucose and impaired glucose tolerance) in adults in Sri Lanka. Projections for the year 2030 and factors associated with diabetes and pre-diabetes are also presented. METHODS: This cross-sectional study was conducted between 2005 and 2006. A nationally representative sample of 5000 adults aged >or= 18 years was selected by a multi-stage random cluster sampling technique. Fasting plasma glucose was tested in all participants and a 75-g oral glucose tolerance test was performed in non-diabetic subjects. Prevalence was estimated for those > 20 years of age. RESULTS: Response rate was 91% (n = 4532), males 40%, age 46.1 +/- 15.1 years (mean +/- standard deviation). The age-sex standardized prevalence (95% confidence interval) of diabetes for Sri Lankans aged >or= 20 years was 10.3% (9.4-11.2%) [males 9.8% (8.4-11.2%), females 10.9% (9.7-12.1%), P = 0.129). Thirty-six per cent (31.9-40.1%) of all diabetic subjects were previously undiagnosed. Diabetes prevalence was higher in the urban population compared with rural [16.4% (13.8-19.0%) vs. 8.7% (7.8-9.6%); P < 0.001]. The prevalence of overall, urban and rural pre-diabetes was 11.5% (10.5-12.5%), 13.6% (11.2-16.0%) and 11.0% (10.0-12.0%), respectively. Overall, 21.8% (20.5-23.1%) had some form of dysglycaemia. The projected diabetes prevalence for the year 2030 is 13.9%. Those with diabetes and pre-diabetes compared with normal glucose tolerance were older, physically inactive, frequently lived in urban areas and had a family history of diabetes. They had higher body mass index, waist circumference, waist-hip ratio, systolic/diastolic blood pressure, low-density lipoprotein cholesterol and triglycerides. Insulin was prescribed to 4.4% (2.7-6.1%) of all diabetic subjects. CONCLUSIONS: One in five adults in Sri Lanka has either diabetes or pre-diabetes and one-third of those with diabetes are undiagnosed.